Investigating Tobacco Usage Habits Using Data Mining Approach - Toni Martinović (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
What are smokers' habits today? Do people rather enjoy cigarettes or rolling tobacco? The research made for this study is going to give us the answer on these questions. The main reason which determines smokers' habits is their lifestyle, e.g. it depends whether they are providing enough money for cigarettes because rolling tobacco is noticeable cheaper. The research is fulfilled by participants of different years, employment status and other lifestyle habits. The research will present the smoking habits of respondents conducted through data mining. The data are processed in the Weka software with the help of a decision tree method - to be precise, the J48 algorithm.
Keywords: D81; 330; smokers; habits; tobacco; cigarettes; data mining; WEKA; J48 algorithm; decision trees